Structure, Composition and Diversity of Tree Vegetation in Sal Mixed Dry Tropical Forest in Chhattisgarh Plains of India - Bijalwan, Arvind; Swamy, S. L.; Sharma, C. M.; Umrao, Rajiv; Paliwal, Harsh Bodh (Indian Forester, 2011)
Structure composition and diversity of woody vegetation of sal mixed dry tropical forest of hmalamdi watershed in barnawapara sancuary, Raipur district of Chhattisgarh, India was studied in over and uner storey forest in four different aspects, Nine prominent tree species were recorded in over and under storied forest with the predominance of Shorea robusta in all the aspects. In the overstorey(pooled), relative density values ranged from 3.03 to 43.94 and understorey from 0.04 to 42.71, Shorea robusta recorded highest relative density in over and understorey vegetation followed by Madhura indica and Tectona grandis The IVI values ranged from 15.88 to 78.62 in overstorey and 14.28 to 83.89 in understorey. The highest IVI values recorded by Shorea robusta in both over and understorey. The diversity(Shannon index value) ranged 1.28 (northern aspect) tp 1.67 (southern aspect) for overstorey and 1.10 (northern) to 1.59 (western) for understorey. The study illustrated that overstorey tree strata in the forest is more dominant than understorey. The Shamun index, Simpson’s index. Spceies richness, Equitability and Beta diversity values were almost higher in overstorey as compared to unerstorey thereforer the present study reveals the normal regeneration pattern in the forest.